PENGARUH KECERDASAN SPIRITUAL, KECERDASAN EMOSIONAL TERHADAP KETRAMPILAN MANEJERIAL DAN KINERJA UKM - Dessy Balik; Cricela Natalia Joseph; Micrets Agustina Silaya (Fakultas Ekonomi dan Bisnis Universitas Pattimura, 2018)
The substance of this study is to investigate the efficient and effective utilization of intangible resources by Christian entrepreneurs in Ambon city as a determinant of the performance of Small and Medium Enterprises (SMEs). The purpose of this study, (1) To test the direct influence of spiritual intelligence on manejerial skills of Christian entrepreneurs in Ambon City. (2) To test the direct influence of emotional intelligence on manejerial skills of Christian entrepreneurs in Ambon City. (3) Testing the direct influence of entrepreneurial manejerial skills on SME's performance. (4) Examine the direct influence of spiritual intelligence on the performance of SMEs. (5) Examine the direct influence of emotional intelligence on the performance of SMEs. (6) Examining the influence of spiritual intelligence on SMEs performance through entrepreneurial manejerial skills. (7) Examine the effect of emotional intelligence on SME performance through entrepreneurial manejerial skills.The result using Path Analysis resulted (1) Spiritual intelligence proved to have direct positive and significant direct effect to the managerial skill of Christian entrepreneur in Ambon City. (2) Spiritual intelligence proved to have direct positive and significant direct impact on the performance of SMEs of Christian entrepreneurs in Ambon City. (3) Spiritual intelligence proved to positively indirectly affect the performance of SMEs of Christian entrepreneurs in Ambon City through managerial skills (although not dominant influences). (4) Emotional intelligence proved to have direct positive and significant direct impact on the managerial skills of Christian entrepreneurs in Ambon City. (5) Emotional intelligence proved to have a direct positive and direct significant impact on the performance of SMEs of Christian entrepreneurs in Ambon City. (6) Emotional intelligence proved to positively indirectly affect the performance of SMEs of Christian entrepreneurs in Ambon City through managerial skills (although not dominant influences). (7) Managerial skill has proved directly and directly positive to the performance of SMEs of Christian entrepreneurs in Ambon City.Keywords: Spiritual intelligence, emotional intelligence, manejerial skills, SME performance.